A Review of Sustaining Sanitation Services Approach - Muntaha Saad; Mufid al-hadithi; Thaer Jasim; Aymen Yousif; Mohamed Freeshah (Journal of Techniques)
The service sector, including the sanitation service, currently occupies a prominent part of the economic and social development plans. The scale of development of this sector has become a criterion for measuring the progress and development in various countries of the world. Infrastructure services management has been introduced in many countries of the world including some of the leading experts in this field to ensure the sustainable development of the sanitation sector. The aim of this study is to systematically review the literature on sanitation to provide an overview of how researchers approach problem solving to achieve sustainability in sanitation services, it was also found that recent studies tend to use geographic information systems (GIS) to analyze sanitation services. Studies using GIS technology have provided maps that can be used as a decision support tool for governmental and non-governmental organizations to prioritize sanitation in underserved areas.